ORIGINEA NATURII UMANE – FUNDAMENT PENTRU CREDINCIOȘII ADVENTIȘTI DE A-ȘI CĂUTA ȘI APĂRA LIBERTATEA RELIGIOASĂ ÎNTRE ANII 1940–1944 (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Origin of Human Nature — A Foundation for Adventist Believers to Seek and Defend Religious Freedom Between 1940-1944.Seventh-day adventist were convinced of the divine origin of human nature, and they saw it as a foundation for human rights in religion. Arriving on Romanian soil, the first Adventist missionaries were to come into contact with the native population. Initially, these missionaries preferred to seek out and address existing Baptist or Protestant believers in various localities, due to the doctrinal and religious practice that existed between their faiths and only in a second stage did Adventist missionaries they were directed to believers of other denominations, especially the Orthodox. In their attempt to make room for their faith to penetrate the local population, they clashed with the conservative spirit of the majority church.